Genome-wide identification of Aedes albopictus long noncoding RNAs and their association with dengue and Zika virus infection. - Azali Azlan; Sattam M Obeidat; Kumitaa Theva Das; Muhammad Amir Yunus; Ghows Azzam (PLoS Neglected Tropical Diseases, 2021)
The Asian tiger mosquito, Aedes albopictus (Ae. albopictus), is an important vector that transmits arboviruses such as dengue (DENV), Zika (ZIKV) and Chikungunya virus (CHIKV). Long noncoding RNAs (lncRNAs) are known to regulate various biological processes. Knowledge on Ae. albopictus lncRNAs and their functional role in virus-host interactions are still limited. Here, we identified and characterized the lncRNAs in the genome of an arbovirus vector, Ae. albopictus, and evaluated their potential involvement in DENV and ZIKV infection. We used 148 public datasets, and identified a total of 10, 867 novel lncRNA transcripts, of which 5,809, 4,139, and 919 were intergenic, intronic and antisense respectively. The Ae. albopictus lncRNAs shared many characteristics with other species such as short length, low GC content, and low sequence conservation. RNA-sequencing of Ae. albopictus cells infected with DENV and ZIKV showed that the expression of lncRNAs was altered upon virus infection. Target prediction analysis revealed that Ae. albopictus lncRNAs may regulate the expression of genes involved in immunity and other metabolic and cellular processes. To verify the role of lncRNAs in virus infection, we generated mutations in lncRNA loci using CRISPR-Cas9, and discovered that two lncRNA loci mutations, namely XLOC_029733 (novel lncRNA transcript id: lncRNA_27639.2) and LOC115270134 (known lncRNA transcript id: XR_003899061.1) resulted in enhancement of DENV and ZIKV replication. The results presented here provide an important foundation for future studies of lncRNAs and their relationship with virus infection in Ae. albopictus.